Internal determinants of Waqaf in non-Muslim countries - Mohamad, Nor Asiah; Faris, Waleed Fekry (2016)

(untitled)
There are many challenges in Waqf Management especially in the Muslim minorities countries. This paper analyses some of the internal challenges faced by the Muslims, either waqf manager or waqf beneficiaries and trustees in their strive to enliven and utilised in the non-Muslim countries. The findings show that the awareness among the Muslim in non-Muslim countries is still low, the management revolves around the traditional uses of waqf while the foreign legal framework still stands as an obstacle to the development and implementation of waqf. There is a need for a concerted effort in preparing a manual of waqf management in the non-Muslim countries with a special account on the fiqh-jurisprudence fitting the contemporary needs and challenges.